Treatment of Cardiovascular Dysfunction With PDE5-Inhibitors – Temperature Dependent Effects on Transport and Metabolism of cAMP and cGMP - Selli, Anders L.; Kuzmiszyn, Adrina K.; Smaglyukova, Natalia; Kondratiev, Timofei V.; Fuskevåg, Ole-Martin; Lyså, Roy A.; Ravna, Aina W.; Tveita, Torkjel; Sager, Georg; Dietrichs, Erik S. (Frontiers in Physiology, 2021)
Introduction: Cardiovascular dysfunction is a potentially lethal complication of hypothermia. Due to a knowledge gap, pharmacological interventions are not recommended at core temperatures below 30°C. Yet, further cooling is induced in surgical procedures and survival of accidental hypothermia is reported after rewarming from below 15°C, advocating a need for evidence-based treatment guidelines. In vivo studies have proposed vasodilation and afterload reduction through arteriole smooth muscle cGMP-elevation as a favorable strategy to prevent cardiovascular dysfunction in hypothermia. Further development of treatment guidelines demand information about temperature-dependent changes in pharmacological effects of clinically relevant vasodilators. Materials and methods: Human phosphodiesterase-enzymes and inverted erythrocytes were utilized to evaluate how vasodilators sildenafil and vardenafil affected cellular efflux and enzymatic breakdown of cAMP and cGMP, at 37°C, 34°C, 32°C, 28°C, 24°C and 20°C. The ability of both drugs to reach their cytosolic site of action was assessed at the same temperatures. IC50- and Ki-values were calculated from dose response curves at all temperatures, to evaluate temperature-dependent effects of both drugs. Results: Both drugs were able to reach the intracellular space at all hypothermic temperatures, with no reduction compared to normothermia. Sildenafil IC50 and Ki-values increased during hypothermia for enzymatic breakdown of both cAMP (IC50: 122 ± 18.9 µM at 37°C vs 269 ± 14.7µM at 20°C, p<0.05) and cGMP (IC50: 0.009 ± 0.000 µM at 37°C vs. 0.024 ± 0.004 µM at 32°C, p<0.05), while no significant changes were detected for vardenafil. Neither of the drugs showed significant hypothermia-induced changes in IC50 and Ki-values for inhibition of cellular cAMP and cGMP efflux. Conclusion: Sildenafil and particularly vardenafil were able to inhibit elimination of cGMP down to 20°C. As the cellular effects of these drugs can cause afterload reduction, they show potential in treating cardiovascular dysfunction during hypothermia. As in normothermia, both drugs showed higher selectivity for inhibition of cGMP-elimination than cAMP-elimination at low core temperatures, indicating that risk for cardiotoxic side effects is not increased by hypothermia.